Glucopuncture for Postherpetic Neuralgia: A Clinical Case - Kersschot , Jan; Karavani , Ilan (Current Progress in Medicine and Medical Research Vol. 6, 2023)
This chapter discuss about a clinical case report on Glucopuncture for Postherpetic Neuralgia. Postherpetic neuralgia (PHN) is the most common complication of herpes zoster (HZ) or ‘shingles’ and affects a significant proportion of HZ patients with the disease, with the elderly being most frequently and seriously affected. PHN is associated with significant loss of function and reduced quality of life, particularly in the elderly, and is highly resistant to treatment. This clinical case describes the treatment of an 88-year-old patient with PHN who continued to suffer from pain for several months despite oral and transdermal pain treatment. The exact mechanism of action of isotonic glucose injections is likely multifactorial. Regulation of neural inflammation and upregulation of pro-inflammatory cytokines are described as effects of glucose injections. Multiple intradermal glucose 5% injections allowed her to discontinue her pain medication regimen after four sessions. The treatment modality is obviously inexpensive and safe, it is unclear why it is still underused. Having a scientific explanation of the mode of action might be helpful, as well as some well-designed clinical studies.